A Putative Frizzled 7‑Targeting Compound Acts as a Firefly Luciferase Inhibitor - Kinsolving, Julia; Grätz, Lukas; Voss, Jan Hendrik; Löw, Bente; Shorter, Emily; Jude, Baptiste; Lanner, Johanna T.; Löber, Stefan; Gmeiner, Peter; Schulte, Gunnar (Journal of Medicinal Chemistry, 2024)
The Frizzled family (FZD1-10) of G protein-coupled receptors regulates WNT signaling mediating proliferative input. Dysregulation of FZD7 and exaggerated WNT/β-catenin signaling is frequently observed in intestinal cancers. Therefore, it is attractive to develop therapeutics targeting FZD7 for cancer treatment. Structure-based virtual screening has identified compound 28, which inhibited WNT/β-catenin signaling based on the luciferase-based reporter gene TOPFlash assay. However, upon pharmacological validation, compound 28 rather acts as a potent Firefly luciferase (Fluc) inhibitor (IC50 = 30 nM), matching the reported IC50 for compound 28-mediated inhibition in the TOPFlash assay. Moreover, we employed Fluc-independent assays, a FZD7-focused bioluminescence resonance energy transfer biosensor and quantitative PCR, to emphasize the inability of compound 28 to inhibit the WNT-3A-induced conformational dynamics in FZD7 and transcription of Axin2, a WNT target gene. Thus, we underline the importance of counter screens to validate compounds that interfere with the detection technology used for compound screening.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Assays; Bioluminescence; Bioluminescent Probes; Drug Discovery; Genetics